2002
DOI: 10.1074/jbc.m205532200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Kv2.1 Voltage-dependent K+Channels in Pancreatic β-Cells Enhances Glucose-dependent Insulin Secretion

Abstract: Voltage-dependent (Kv) outward K ؉ currents repolarize ␤-cell action potentials during a glucose stimulus to limit Ca 2؉ entry and insulin secretion. Dominant-negative "knockout" of Kv2 family channels enhances glucose-stimulated insulin secretion. Here we show that a putative Kv2.1 antagonist (C-1) stimulates insulin secretion from MIN6 insulinoma cells in a glucose-and dosedependent manner while blocking voltage-dependent outward K ؉ currents. C-1-blocked recombinant Kv2.1-mediated currents more specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
171
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 49 publications
8
171
0
1
Order By: Relevance
“…This would be similar to the well-known effect of inhibiting beta cell Kv currents on insulin secretion, even with very high concentrations (20 mmol/l) of TEA [11,16,20]. We found that alpha cell Kv currents are inhibited by low millimolar levels of TEA and 4-aminopyridine.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This would be similar to the well-known effect of inhibiting beta cell Kv currents on insulin secretion, even with very high concentrations (20 mmol/l) of TEA [11,16,20]. We found that alpha cell Kv currents are inhibited by low millimolar levels of TEA and 4-aminopyridine.…”
Section: Discussionsupporting
confidence: 87%
“…Notably, we did not observe the TEA-resistant rapidly inactivating current component reported previously in isolated alpha cells [19] and alpha cells from intact islets [3]. In beta cells, inhibition of Kv currents with TEA augments insulin secretion in a glucose-dependent manner, since Kv channels contribute to action potential repolarisation [11,16,20]. Since alpha cells are electrically active at low glucose [3,4,21], we hypothesised that inhibition of Kv currents at low glucose concentrations should enhance glucagon secretion under this condition, due to action potential prolongation as is the case for beta cell insulin secretion.…”
Section: Methodsmentioning
confidence: 45%
“…Our observations suggest that Kv2.1 might represent one such channel. The PLA 2 product AA blocks the activity of these channels, and overexpression of iPLA 2 ␤ in insulinoma cells is associated with amplification of insulin secretion and suppression of Kv2.1 channel activity, which is consistent with previous observations that blockade of Kv2.1 activity by other means also results in increased insulin secretory responses (48,49).…”
Section: Discussionsupporting
confidence: 80%
“…Reducing Kv current prolongs stimulus-induced depolarization of the ␤-cell plasma membrane and thereby amplifies insulin secretion (46,48). This could account for the observations that overexpression of iPLA 2 ␤ in insulinoma cells is associated with both amplified insulin secretion (21) and reduced Kv2.1 channel activity (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation